Clinical considerations for speech-language pathologists in the treatment of people with COVID-19 and tracheostomy. Part II: Improving phonation to facilitate communication - Tobar-Fredes, Rodrigo; Briceño Meneses, Belén; Venegas-Mahn, Macarena; Orellana Villouta, Marisis; Fuentealba Miranda, Inés; Pavez Reyes, Axel; González Varas, Ariela; Wang, Ying; Vera-González, Rocío; Vásquez Lara, Pablo; Saá-Barra, Nelson; Zúñiga Reyes, Javiera; et al. (Revista Chilena de Fonoaudiología, 2020)
The COVID-19 disease was declared a pandemic by the World Health Organization. When most severe, it generates a condition that requires treatment in intensive care units, which, when extended in time, requires implementing of a tracheostomy to facilitate invasive ventilatory support. Although ventilatory support has important advantages that favor recovery and rehabilitation, it generates various complications for patients’ communication, a condition that adds to the effects of COVID-19 and the frequent history of previous endotracheal intubation. The aim of this article is to provide guidance and clinical tools for the treatment of phonation to facilitate communication in people with tracheostomy and COVID-19. For this, the recommendations of the existing available literature are considered, under a pragmatic analysis and based on our experience of treating more than 561 infected patients. The characteristics of communication in this population, its treatment, considerations for the use of specific techniques and guidelines to improve quality of life are exposed. Always with an approach oriented to the care and protection of users and the health team, in particular speech-language pathologists in the country.